Numerical studies on the pressure-retarded osmosis (PRO) system with the spiral wound module for power generation - Hong, Sung-Soo; Ryoo, Won; Chun, Myung-Suk; Lee, Seung Oh; Chung, Gui-Yung (DESALINATION PUBL, 2014)
The pressure-retarded osmosis system with the spiral wound module for power generation has been studied numerically. The system includes draw channel, membrane, and feed-channel. The water flux and the solute flux across membrane were calculated. In addition, changes in concentration, flow rate, and pressure of channel-fluids were obtained. Water flux across membrane decreases about 10% along the direction of draw-fluid in our system and increases slightly along the direction of feed-fluid. The concentration of draw-fluid decreases along the direction of draw-fluid. Power density is almost proportional to the inlet concentration difference, and increases at first and then decreases as the difference between inlet pressures of feed- and draw-fluids increases.
Keywords: ANALYTICAL-MODEL; REVERSE; PERFORMANCE